Chloroplast genome of Tillandsia marconae till & Vitek (Bromeliaceae), a hyperarid desert endangered species - Chávez Galarza, Julio César (2021)
Tillandsia marconae Till & Vitek (Bromeliaceae) is a rare plant native species that grows over sand, in the coastal desert from Perú and Chile and is considered an endangered species. In this study, we assembled its chloroplast genome. The draft chloroplast genome of T. marconae is ca. 158,873 bp in length, containing a large single-copy region of 86,937 bp, a small single-copy region of 18,506 bp, and a pair of inverted repeat regions of 26,715 bp. The GC content of the draft chloroplast genome is 37.4%. It encodes a total of 135 genes, including 86 protein-coding genes, 38 tRNA genes, 8 rRNA genes, and three pseudogenes. The phylogenetic tree indicated that T. marconae is placed within the Bromeliaceae family and a close relationship with Tillandsia usneoides with 100% support.